A Straightforward Assay for Screening and Quantification of Biosurfactants in Microbial Culture Supernatants - Kubicki, Sonja; Bator, Isabel; Jankowski, Silke; Schipper, Kerstin; Tiso, Till; Feldbrügge, Michael; Blank, Lars M.; Thies, Stephan; Jaeger, Karl-Erich (Frontiers in Bioengineering and Biotechnology, 2020)
A large variety of microorganisms produce biosurfactants with the potential for a number of diverse industrial applications. To identify suitable wildtype or engineered production strains, efficient screening methods are needed allowing for rapid and reliable quantification of biosurfactants in multiple cultures, preferably at high throughput. To this end, we have established a novel and sensitive assay for the quantification of biosurfactants based on the dye Victoria Pure Blue BO (VPBO). The assay allows the colorimetric assessment of biosurfactants directly in culture supernatants and does not require extraction or concentration procedures. Working ranges were determined for precise quantification of different rhamnolipid biosurfactants; titers in culture supernatants of recombinant Pseudomonas putida KT2440 calculated accordingly were confirmed by independent HPLC-CAD analyses. The assay was successfully applied for detection of chemically different an- or non-ionic biosurfactants including mono- and di-rhamnolipids (glycolipids), mannosylerythritol lipids (MELs, glycolipids), 3 (3 hydroxyalkanoyloxy) alkanoic acids (fatty acid conjugates), serrawettin W1 (lipopeptide), and N acyltyrosine (lipoamino acid). In summary, the VPBO assay offers a broad range of applications including the comparative evaluation of different cultivation conditions and high-throughput screening of biosurfactant producing microbial strains.